OPINI PUBLIK TERHADAP PROGRAM SIARAN BERITA DI RADIO PEMERINTAH KABUPATEN SIAK - Hadi Yusri; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
RPK Siak is now more often used as an entertainment media, even though the radio also serves as a medium of information and educative. Furthermore, about the growing opinion in the midst of society such as moving the radio frequency when broadcasting news, news conveyed in the capture of newspaper / newspaper published on that day, the broadcasters are less well able to read the news, or news which aired more many national news than local news. This study aims to determine how public opinion on the news program in RPK Siak, and to investigate the factors that influence the inhibiting and supporting programs in RPK Siak newscast.The study uses descriptive qualitative method of data collection techniques of observation, interviews (interviews) and documentation. The informants in this study is a community located in Siak and also the staff RPK Siak using purposive sampling technique to check the validity of the data, the authors use the extension of participation and triangulation techniques ..The results of this study indicate first, the formation of public opinion is due to cultural background, past experience, espoused values, and issues emerging through the process of formation of understanding, feelings, behavior and become the same konsesnus forming opinions such public radio news from the news content (up to date news delivered or not), and how the delivery of the news itself (announcer). Second, the factors inhibiting and supporters. Factors supporting mempengruhi news broadcasts programs in RPK Siak is with public facilities and infrastructure available. While it is a factor inhibitors, the news is often too late, more national news, and broadcaster RPK should be improved skills.Keyword : Public Opinion, News Program, Public Radio